2005
DOI: 10.1143/jjap.44.2307
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post CF4 Plasma Treatment on the HfO2 Thin Film

Abstract: In this study, a novel approach was proposed to improve the characterization of HfO 2 . Fluorine was incorporated by CF 4 plasma to improve the HfO 2 gate dielectric properties including leakage current, breakdown voltage and hysteresis. The hysteresis of capacitance-voltage characteristics can be reduced to approximately 10% hysteresis voltage for the samples with CF 4 plasma treatment. An inner-interface trapping model is presented to explain the hysteresis. The secondary-ion mass spectroscopy (SIMS) results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 9 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…The sensitivity of the nanowire sample posttreated with N 2 is higher than those of nanowire samples posttreated with NH 3 and those that did not receive treatment. Several studies have reported the successful incorporation of nitrogen into the interfacial layer (IL) and dielectric layer of high-material [33][34][35][36]. Hence, plasma treatment was effective for incorporating nitrogen on the SiGe nanowire surface.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of the nanowire sample posttreated with N 2 is higher than those of nanowire samples posttreated with NH 3 and those that did not receive treatment. Several studies have reported the successful incorporation of nitrogen into the interfacial layer (IL) and dielectric layer of high-material [33][34][35][36]. Hence, plasma treatment was effective for incorporating nitrogen on the SiGe nanowire surface.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the capacitance density and interface characteristics show further improvement with the combination of CF 4 pre-treatment for 10 sec and N 2 post-treatment for 120 sec. With CF 4 pre-treatment, fluorine atoms would pile up at the HfO 2 /Si interface, improve the quality of interface [19], and suppress the IL formation [20]. Besides, for CF 4 pre-treatment times longer than 10 sec, the plasma damage caused the degradation of HfO 2 /Si interface and the degradation of capacitance density.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18] It has been reported that on Si substrate, F tends to segregate to the HfO 2 / SiO 2 and SiO 2 / Si interfaces passivating oxygen vacancy and interface traps by forming stronger Hf-F and Si-F bonds. 13 On Ge substrate, formation of Ge-F and Hf-F bonds at the high / Ge interface and in the HfO 2 gate dielectric results in less interface and bulk traps, respectively.…”
Section: Effects Of Fluorine Incorporation Into Hfo 2 Gate Dielectricmentioning
confidence: 99%
“…Insufficient plasma treatment might not improve the gate dielectric quality, and excessive plasma treatment possibly causes plasma damage and corrodes the improvement. 17,18 Figure 3 compares the SS and hysteresis for the HfO 2 / InP gate stack with different CF 4 rf powers for 3 min. SS for the control sample, samples with 20 W treatment, and samples with 30 W treatment are 120 mV/dec, 106.6 mV/dec, and 97.1 mV/dec, respectively.…”
Section: Effects Of Fluorine Incorporation Into Hfo 2 Gate Dielectricmentioning
confidence: 99%